Harnessing Teams and Technology to Improve Outcomes in Infants With Single Ventricle. (May 2016) - Shirali, Girish; Erickson, Lori; Apperson, Jonathan; Goggin, Kathy; Williams, David; Reid, Kimberly; Bradley-Ewing, Andrea; Tucker, Dawn; Bingler, Michael; Spertus, John; Rabbitt, Leslie; Stroup, Richard
Abstract : Infants with single ventricle require staged cardiac surgery, with stage I typically performed shortly after birth, stage II at 4 to 6 months of age, and stage III at 3 to 5 years of age. There is a high risk of interstage mortality and morbidity after infants are discharged from the hospital between stages I and II. Traditional home monitoring requires caregivers to record measurements of weight and oxygen saturation into a binder and requires families to assume a surveillance role. We have developed a tablet PC–based solution that provides secure and nearly instantaneous transfer of patient information to a cloud-based server, with the capacity for instant alerts to be sent to the caregiver team. The cloud-based IT infrastructure lends itself well to being able to be scaled to multiple sites while maintaining strict control over the privacy of each site. All transmitted data are transferred to the electronic medical record daily. The system conforms to recently released Food and Drug Administration regulation that pertains to mobile health technologies and devices. Since this platform was developed in March 2014, 30 patients have been monitored. There have been no interstage deaths. The experience of care providers has been unanimously positive. The addition of video has added to the use of the monitoring program. Of 30 families, 23 expressed a preference for the tablet PC over the notebook, 3 had no preference, and 4 preferred the notebook to the tablet PC. Abstract : Supplemental Digital Content is available in the text.